Tinjauan Yuridis Pelibatan TNI dalam Pemberantasan Tindak Pidana Teroris Dihubungkan dengan UU No.5 Tahun 2018 tentang Perubahan UU No 15 Tahun 2003 tentang Perpu No. 1 Tahun 2002 tentang Pemberantasan Tindak Pidana Terorisme - Muhammad Arbi Alghiyats; Dini Dewi Heniarti (UNISBA Press, 2022)
Abstract. Law enforcement is believed to guarantee and protect the interests of the community. Terrorism is a crime whose effects are truly extraordinary. In Article 7 paragraph (2). Furthermore, Law Number 5 of 2018 concerning the eradication of criminal acts of terrorism in Article 431 mentions the involvement of the TNI in handling criminal acts of terrorism. The enforcement of criminal law against perpetrators of criminal acts of terrorism in Indonesia is regulated in Articles 6, 7, 13 and 14 of Law No. 5 of 2018. Then the Role and Function of the TNI in handling terrorism as Article 43I of Law No. 5 of 2018 is a form of handling military operations other than war. which refers to articles 6 and 7 paragraph (2) letter b of Law No. 34 concerning the TNI and at the request of the police or the government in accordance with Article 41 of Law No. 2022 concerning the Indonesian National Police, their involvement in the context of the scale of the threat of terrorism that already threatens state sovereignty or cannot be handled again by the police.. Abstrak. Penegakan hukum diyakini untuk menjamin dan melindungi kepentingan masyarakat. Terorisme merupakan kejahatan yang mana efek yang ditimbulkannya benar-benar sangat luar biasa dirasakan.Dalam Pasal 7 ayat (2). Selanjtnya Undang-Undang Nomor 5 tahun 2018 tentang pemberantasan tindak pidana terorisme pada Pasal 431 menyebutkan akan keterlibatan TNI dalam penangana tindak pidana terorisme. Penegakan hukum pidana terhadap para pelaku tindak pidan terorisme di Indonesia diatur dalam Pasal 6,7,13 dan 14 UU No 5 tahun 2018. Kemudian Peran dan Fungsi TNI dalam penanganan terorisme sebagiamana Pasal 43I UU no 5 tahun 2018 merupakan bentuk penangan oprasi militer selain perang yang mengacu pada pasal 6 dan 7 ayata (2) huruf b UU No 34 tentang TNI dan atas dasar permintaan kepolisian atau pemerintah sesuai pasal 41 UU No 2022 tentang Kepolisian RI maka keterlibatannya dalam konteks skala ancaman terorisme yang sudah mengancam kedaulatan negara atau tidak dapat ditangani lagi oleh kepolisian.